Youth gangs, racism, and schooling : Vietnamese American youth in a postcolonial context - Lam, Kevin D. (Palgrave Macmillan's postcolonial studies in education., 2015)
"Youth Gangs, Racism, and Schooling examines Vietnamese American youth gang formation in Southern California, with an emphasis on the experiences of those heavily involved in the 1990s. Lam traces the genealogy of the Vietnamese American youth gang phenomenon as part of the conflict in Southeast Asia. He describes the consequences of war and migration for youth as well as their racialization as "Asian-American" subjects. Grounded in the critical narratives of three gang members, Lam addresses themes of racism, violence, class struggle, style, and schooling in an era of anti-youth and anti-immigration legislation in the state and nationally. In this dehumanizing context, Lam frames Vietnamese and Southeast American gang members as post-colonial subjects, offering an alternative analysis toward humanization and decolonization"--